Deciphering Timira: A Critical appraisal of Visual Pathologies in Ayurveda - thakur , Akanksha Thakur; kumar goud , Prem; rajagopala , Manjusha (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Visual disturbances are prevalent in ophthalmic practice, significantly impacting daily life. Ayurveda classifies such disorders under Drishtigata Rogas, with Timira being a primary condition characterized by progressive vision loss due to Dosha accumulation in the eye’s Patalas (layers). Methods: This review analyzes classical Ayurvedic texts – Sushruta Samhita, Charaka Samhita, and Ashtanga Hridaya—to elucidate Timira’s etiology, pathogenesis, and clinical features. The Nidana Panchaka framework (causative factors, prodromal symptoms, clinical features, therapeutic assessment, and pathogenesis) guides the understanding of Timira’s progression and management. Results: Timira progresses as vitiated Doshas ascend through Rupavaha Siras into the ocular Patalas, causing sequential visual deterioration across four stages – from blurred vision (early refractive errors) to complete blindness (optic nerve damage). Dosha-specific features include Vataja: motion-like haziness, Pittaja: Light flashes and halos, Kaphaja: dull, cloudy vision, and Raktaja: multicolored darkness. These manifestations align with modern conditions, such as myopia, cataracts, and retinal diseases. Conclusion: Ayurveda’s detailed classification of Timira offers a comprehensive framework for understanding visual disorders. The correlation between Timira’s stages and modern ophthalmic conditions underscores the potential of integrative approaches in diagnosis and treatment, bridging traditional knowledge with contemporary eye care practices. Visual disturbances are among the most common complaints presented by patients in ophthalmic outpatient departments, which can impact daily functioning. In Ayurvedic literature, such disturbances are classified primarily under Timira, Kacha, and Linganasha, as described by all major Acharyas. Acharya Sushruta enumerates 12 types of Dṛiṣhṭigata Rogas (diseases affecting the visual apparatus), while Acharya Vagbhaṭa describes 27. Among these, Timira is considered a significant clinical entity under the broad category of Dṛiṣhṭigata Rogas. Acharya Sushruta regards Timira as a Ghora Roga (grave disorder), characterized by progressive visual disturbance due to the